2022
DOI: 10.1021/acsnano.2c09181
|View full text |Cite
|
Sign up to set email alerts
|

AgNPs-Triggered Seed Metabolic and Transcriptional Reprogramming Enhanced Rice Salt Tolerance and Blast Resistance

Abstract: Seeds are facing harsher environments due to the changing climate. Improving seeds' stress resilience is critical to reduce yield loss. Here, we propose that using ROS-generating nanoparticles (NPs) to prestimulate seeds would enhance the stress resilience of seeds and seedlings through triggering stress/immune responses. We examined this hypothesis by exposing AgNPs-primed rice (Oryza sativa L.) seeds under salt conditions (NaCl). The results showed that primed seeds exhibit accelerated germination speed, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…31 It was found that Ag NPs restimulate seeds, which would enhance the salt stress resilience of seeds and seedlings through triggering stress/ immune responses. 32 And in a previous report, we found that biochar NPs improved rice resistance to ferulic acid which is the major allelochemical from invasive plants. 29 And it is confirmed that nanomaterials have a high surface area to volume ratio, which makes them attractive for adsorbing chemicals onto their surface via van der Waals forces, electrostatic interactions, or chemical bonding.…”
Section: Introductionmentioning
confidence: 74%
“…31 It was found that Ag NPs restimulate seeds, which would enhance the salt stress resilience of seeds and seedlings through triggering stress/ immune responses. 32 And in a previous report, we found that biochar NPs improved rice resistance to ferulic acid which is the major allelochemical from invasive plants. 29 And it is confirmed that nanomaterials have a high surface area to volume ratio, which makes them attractive for adsorbing chemicals onto their surface via van der Waals forces, electrostatic interactions, or chemical bonding.…”
Section: Introductionmentioning
confidence: 74%
“…Our recent studies have demonstrated that AgNPs can penetrate the seed coat and enter into rice seed tissues, catalyzing ROS generation during the training process . However, whether AgNPs enter rice leaves and catalyze ROS production during leaf training is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies have demonstrated that AgNPs can penetrate the seed coat and enter into rice seed tissues, catalyzing ROS generation during the training process. 54 However, whether AgNPs enter rice leaves and catalyze ROS production during leaf training is unknown. Previous studies have demonstrated that nanoparticles in the size range of ∼50−70 nm are able to enter into leaves through leaf stomata and cuticular pathways.…”
Section: Acsmentioning
confidence: 99%
“…61 Additionally, seed germination is initiated by water absorption (imbibition) through small pores in the seed coat, such that SiO 2 NPs may enter seeds as a suspension in the imbibed water. 62 SiO 2 NPs that have entered seeds may subsequently be transported from the roots to the buds during plant growth. The penetration and translocation of SiO 2 NPs in the radicle, root, and leaf tissues of SiO 2 NP-primed seedlings have been demonstrated using SEM.…”
Section: Sio2 Np Accumulation In Plantsmentioning
confidence: 99%